TSH Level In Type 2 Diabetes Mellitus Patients In Different Age Groups And The Effect Of Treatment (The Review of Diabetic Studies, 2025)
Background:Type 2 diabetes mellitus (T2 DM) is frequently associated with thyroid dysfunction, particularly alterations in Thyroid Stimulating Hormone (TSH). Understanding the relationship between T2DM, age, and treatment on thyroid function is crucial for improving patient outcomes.Objective: This study aimed to compare TSH levels between patients with T2DM and healthy controls, stratified by age groups, and to investigate the impact of different therapeutic regimens on thyroid function.Methods:  This is a cross sectional study,  carried out during the period of December 2023 to February 2024.A total of (66) patients  with T2DM and age -matched(33) healthy controls were enrolled. Participants were divided into three age groups (30–40, 40–50, and 50+ years). Serum TSH levels were measured using standard immunoassay methods. Statistical analysis included descriptive measures and independent t-tests for comparisons. Treatment-related differences were also analyzed.Results:The results  showed significantly  higher mean TSH levels in diabetic patients compared to controls (p = 0.031). Age-stratified analysis revealed that patients over 50 years exhibited the highest TSH values, indicating an age-related exacerbation of thyroid dysfunction in T2DM. Regarding treatment effects, metformin-based therapy was associated with elevated TSH levels, while sulfonylureas showed variable responses and SGLT2 inhibitors demonstrated the lowest TSH levels, though sample size was limited. These findings underscore the intricate  interactions among diabetes, thyroid function,age, and pharmacotherapy.Conclusion: TSH levels in T2DM patients exhibit variability influenced by age and treatment, indicating the intricate relationship between diabetes and thyroid function. To get the best care for diabetic patients, especially older ones and those on certain treatment plans, it is important to check their thyroid status regularly.